Membran Filtrasyonun Beyaz Peynir Üretiminde Bileşim Ve Kalite Üzerine Etkisinin İncelenmesi - Çınar, Kadir (Fen Bilimleri Enstitüsü, 2015)
Bu araştırmanın amacı mikrofiltrasyon ile zenginleştirilmiş süt retentatlarının salamura beyaz peynire işlenmesi sonucu elde edilen peynirlerin bileşim ve kalite özelliklerinin incelenmesidir. Bu amaçla, peynire işlenecek sütün zenginleştirilmesi için biri 0,05 μm gözenek boyutuna sahip polietersülfon (MP005), diğeri ise 0,20 μm gözenek boyutuna sahip polivilidenflorid (MV020) olmak üzere iki çeşit mikrofiltrasyon membranı kullanılmıştır. SEPA CF-II laboratuvar ölçekli, düz tabakalı membran test ünitesi kullanılarak MP005 membranda 1,59, 1,71, 1,85, 1,93 zenginleştirme faktörlerinde, MV020 membranda ise 1,24 zenginleştirme faktöründe çalışılmıştır. Zenginleştirme sonucu elde edilen permeat ve retentat hatları kimyasal bileşim açısından değerlendirilmiştir.  Salamura beyaz peynir örnekleri doğrudan günlük sütten ve mikrofiltrasyon retentatlarından olmak üzere iki ayrı yöntemle elde edilmiştir. Doğrudan günlük sütten elde edilen peynir kontrol örneği olarak kullanılmıştır. Elde edilen peynirler ve peyniraltı suyunun kimyasal bileşimleri de ayrıca incelenmiştir. Elde edilen peynir örnekleri renk (L*, a*, b*), tekstür (sertlik, tutunabilirlik, elastikiyet, yapışkanlık, sakızımsızlık, çiğnenebilirlik, esneklik) ve duyusal (renk, koku, kitle-yapı, lezzet) özellikler açısından incelenmiştir. Duyusal özellikler eğitilmemiş 14 kişilik bir panelist grubuyla sıralama-puanlama yöntemi kullanılarak gerçekleştirilmiş, karşılaştırmalar için Duncan çoklu karşılaştırma testi (p

Turkish white cheese is a kind of brined cheese and it is the most popular traditional cheese in Turkey. It has soft or semi-hard texture and a salty, acid taste. There are similar types of Turkish white cheese around the world such as Bulgaria’s Sirene, Romania’s Telamme, Greece’s Feta,Yugoslavia’s  Primonski Sir and Grobniciki  Sir,  Israel’s Brinsa, America’s Queso Blanco and  Pickle  Cheese  and  Egypt’s Domiati  cheese.  Membrane filtration techniques are used in the milk industry for several purposes such as fractionation of milk fat from whole milk, removal of bacteria and spores from milk, standardization or enrichment of protein content of the milk etc. Membrane filtration techniques are readily used in cheese production, since cheese production is actually a kind of concentration (enrichment) process. Ultrafiltration and microfiltration are the major membrane processes employed in the cheese industry. These filtration processes are used to produce cheese from milk retentates. Ultrafiltration has been applied to cheese production over the past 45 years, whereas microfiltration is a more recent technology. Although ultrafiltration offers some benefits in cheese manufacturing such as improvement in hygienic capacity, minimal heating, increased cheese yield, homogeneity of the quality of the final cheese product, it is observed to have negative impacts on cheese quality due to the enrichment of whey proteins in the ultrafiltrated milk. However, in microfiltration larger membrane pore sizes are used. For this reason, the enrichment of whey proteins in cheese milk is less. Milk is a complex mixture of different components such as fat, protein, lactose, minerals, etc. These components have unique nutritional and functional characteristics. Whey proteins represent approximately 20 % of the milk proteins. In traditional cheese production whey proteins remain in the whey with fat, caseinomacropeptides, rennet, etc. For this reason, purification or concentration of whey proteins is difficult and expensive. Also, whey has low solid content and high biological oxygen demand (BOD), which creates a major disposal problem. On the other hand, the permeate stream obtained after microfiltration of milk is referred to as “ideal whey” since it contains whey proteins that do not contribute to the cheesemaking process. Thus, unlike classical whey, ideal whey has sterile native components with higly functional properties and also no fat in its composition. The presence of fat in whey leads to decreased functional properties and shorter storage life. Moreover, microfiltered whey proteins maintain their biological activity and have a better flavor profile than classical whey. Therefore, ideal whey is a much better raw material for manufacturing high quality whey protein ingredients. The aim of the present study is to investigate the chemical composition and the quality parameters of white brined cheese obtained from pasteurized milk enriched upon microfiltration. For this purpose, two types of microfiltration membranes were used: a polyethersulfone membrane (MP005) with a pore size of 0.05 μm, and a polyvilidene fluoride membrane (MV020) with a pore size of 0.20 μm. Microfiltration equipment used is a laboratory scale SEPA CF-II membrane test unit equipped with a flat plate. Enrichment factors of 1.59, 1.71, 1.85, and 1.93 were achieved with the polyethersulfone membrane, whereas the enrichment factor was 1.24 with the polyvilidene fluoride membrane. Chemical compositions of the permeate and the retentate streams were analyzed with respect to dry matter, protein, fat and ash contents.  White cheese was obtained from the retentate streams enriched upon microfiltration. White cheese obtained directly from pasteurized milk was used as the control sample. Chemical compositions of the white brined cheese samples were analyzed with regard to dry matter, protein, fat, ash, salt contents and acidity. Whey obtained upon cheese making was analyzed with respect to dry matter, protein and ash contents. Color (L*, a*, b*) and texture parameters (hardness, adhesiveness, springiness, cohesiveness, gumminess, chewiness, resilience) of cheese samples including the control were measured and evaluated. Sensory tests with regard to color, odor, texture and flavor performed by 14 untrained panelists by ranking the cheese samples. Sensory test results were evaluated using Duncan Multiple Comparison Test (p
Investigation Of The Effects Of Membran Filtration Techniques On Composition And Quality Of White Brined Cheese
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Türk Beyaz Peyniri; Membran Filtrasyon; Mikrofiltrasyon; Tekstür Profil Analizi; Turkish White Cheese; Membrane Filtration; Microfiltration; Texture Profile Analysis